A split fluorescent reporter with rapid and reversible complementation - Alison G. Tebo (Nature Portfolio, 2019)
Monitoring protein-protein interactions via bimolecular fluorescence complementation is often limited by the slow kinetics and irreversibility of the complementation. Here the authors introduce a fluorescent reporter for real-time monitoring of reversible interactions based on complementation and binding of an exogenous chromophore.